Salivary cortisol, dehydroepiandrosterone, and chromogranin A levels in patients with gingivitis and periodontitis and a novel biomarker for psychological stress - Lee, Yeon-Hee; Suk, Chon; Shin, Seung-Il; Hong, Ji-Youn (Frontiers in Endocrinology, 2023)
Introduction This study aimed to investigate the neuroendocrine responses based on cortisol, dehydroepiandrosterone (DHEA), cortisol/DHEA ratio, and chromogranin A levels, which reflect the activity of the hypothalamic-pituitary-adrenal axis, according to the presence or absence of psychological stress in patients with gingivitis and periodontitis compared to that in healthy controls. Methods In total, 117 patients (60 women, mean age: 36.29 ± 19.03 years) participated in this case-control study, comprising 32 healthy controls, 49 patients with gingivitis, and 36 patients with periodontitis. We investigated the presence of psychological stress and salivary characteristics, and analyzed the stress-related biomarkers of cortisol, DHEA, cortisol/DHEA ratio, and chromogranin A in the stimulated saliva. Results Salivary cortisol and chromogranin A levels increased with the severity of periodontal disease; their levels were the highest in the periodontitis group and were significantly higher in the following descending order: periodontitis, gingivitis, and healthy control groups (all values of p < 0.001). Additionally, the DHEA levels and cortisol/DHEA ratio were higher in the periodontitis group than those in the healthy control group (all values of p < 0.001). A multivariate logistic regression analysis revealed that the factors predicting above-average cortisol levels were periodontitis (odds ratio [OR] = 256.829; p < 0.001), women (OR = 6.365; p = 0.004), and psychological stress (OR = 6.036; p = 0.007); those predicting above-average cortisol/DHEA ratios were periodontitis (OR = 11.436; p < 0.001), psychological stress (OR = 3.977; p = 0.003), and women (OR = 2.890; p = 0.026). Thus, periodontitis and psychological stress were significant and strong predictors of above-average cortisol levels and cortisol/DHEA ratios. In the gingivitis group, salivary cortisol levels (r = 0.381, p = 0.007) and cortisol/DHEA ratios (r = 0.479, p < 0.001) were correlated with the presence of psychological stress. In the periodontitis group, increased cortisol/DHEA ratios (r = 0.412, p = 0.013) and lowered salivary buffer capacities (r = -0.334, p = 0.047) were correlated with the presence of psychological stress. Conclusion Periodontitis is a multifactorial disease resulting in inflammatory tissue destruction, which differs from gingivitis and a healthy state. Differences in stress-related neuroendocrine markers were revealed based on the severity of periodontal disease. The biomarkers that could be classified according to disease severity were salivary cortisol and chromogranin A levels. Above-average cortisol levels and cortisol/DHEA ratios are significant predictors of psychological stress in patients with gingivitis and periodontitis.